Patients' satisfaction in Antenatal Clinic Hospital Universiti Kebangsaan Malaysia - S. Dyah Pitaloka,; A.M. Rizal, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Background: A cross sectional study was carried out to identify the level and factors associated with patients’ satisfaction in antenatal clinic at Hospital Universiti Kebangsaan Malaysia. Methods: A total of 150 respondents were selected by using convenience sampling method. Data was collected via structured questionnaire with face to face interview. The obtained data was analyzed by using SPSS version 11.5. Results: Majority of the respondents were Malay (72%), while Chinese (18%) and Indian (10%). Age of the respondents around 19 to 40 years old with tertiary education level (50.7%) and most of them are working (76.4%). More than half of the respondents were satisfied with the service that they received (56.7%), while the others (43.3%) not satisfied. Generally, most of the respondents were satisfied with interpersonal aspects from the staff (62%), technical quality of the doctors (79.3%), efficacy (78%), availability (50.7%), and the financial aspect (70%). Meanwhile, the respondents were not satisfied with the several aspects i.e. accessibility (61.3%), convenience (51.3%), and continuity of care (81.3%). In bivariate analysis, the result of this study showed that there were only two factors significantly related with level of satisfaction (p<0.05) i.e. charge of service and number of visit. Further analysis, by using multiple logistic regression showed that health status and number of visit were the predictors of the level of satisfaction. Conclusions: This study showed that most of the respondents were satisfied with the service that they received. However, increase number of doctors, improve interpersonal manner and technical quality of the staff especially nurses and improve facilities of the antenatal clinic should be considered to improve overall patients’ satisfaction